“Therapeutic dimension of canonical punishment” – a highlighted principle in the issue of pedophilia in the pastoral care of the Catholic Church - Biały, Stanisław (Prawo Kanoniczne, 2024)
The motive for writing the article were the words of Pope Francis: “The true meaning of the law must be regained in the Church. For although the Word of God and the sacraments play a superior role in it, the legal norm that serves unity also plays an indispensable role in it”. This is what Pope Francis declared during the audience for the participants of the plenary session of the Pontifical Council for Legal Texts, which dealt with the revision of Book VI of the Code of Canon Law, ie on sanctions in the Church. The result of the analysis of the documents in the aspect in which the changes are going are the following conclusions: The Church has established new criteria for punishing paedophilia criminals (more stringent), and is trying to implement these criteria. It is primarily about removing from office, and even removing from the priesthood. Now, the principle of seeking justice is transparency, i.e. the abolition of procedural secrecy, which was previously in force under the penalty of excommunication, and an attempt to redress wrongs caused by clergy to minors (whether in a moral or material sense). The issue of prevention, i.e. preventing criminogenic situations, is also important. This raises hope that the painful relationships resulting from the crimes of paedophilia (committed by clergy) and the concealment of these crimes by their ordinaries will be repaired.